The Preparation of Titanium Dioxide Gas Sensors by the Electric Field Assisted Aerosol CVD Reaction of Titanium Isopropoxide in Toluene - Michael Warwick (Chemical Vapor Deposition, 2012)
Thin films of titanium dioxide are deposited on gas-sensor substrates at 450 °C from the aerosol-assisted (AA)CVD of titanium isopropoxide solutions in toluene under the influence of electric fields. Electric fields are generated by applying a potential difference between the inter-digitated electrodes of the gas-sensor substrate during the deposition. The deposited films are analyzed and characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD), and Raman spectroscopy (RS). It is found that an increase in electric field strength during deposition causes changes in the film microstructure, preferential orientation, and growth rate. The gas-sensor properties of the films are also examined. It is found that applying an electric field during the deposition improves the film microstructure and leads to a two-fold enhancement in the sensing properties of the film.